Absence of correlation between follicular fluid volume and follicular granulocyte colony-stimulating factor, a predictor of embryo implantation and successful delivery. (3rd March 2020) - Noël, Laure; Donneau, Anne-Françoise; Jouan, Caroline; Schoenen, Sophie; Lédée, Nathalie; Foidart, Jean-Michel; Nisolle, Michelle; Munaut, Carine
Abstract: Follicular granulocyte colony-stimulating factor (G-CSF) is a documented marker of embryo implantation potential. The primary objective was to determine whether follicular G-CSF levels correlate with follicular fluid volume. The secondary objectives were to assess whether follicular G-CSF is associated with oocyte maturity at the time of harvest and with delivery rate after fresh or frozen embryo transfer. Thirty-two patients undergoing intracytoplasmic sperm injection (ICSI) cycles were recruited (Centre de Procréation Médicalement Assistée (CPMA), University of Liège, Belgium). A total of 211 follicular fluid (FF) samples were individually collected at the time of oocyte harvest. FF volume was recorded, and G-CSF concentration was assessed by ELISA. The embryos were individually cultured in vitro . Their implantation and live birth rates were recorded after fresh and frozen embryo transfers. The follicular fluid volume did not correlate with the follicular G-CSF concentration. There were no differences in follicular G-CSF levels between mature and immature oocytes. The probability of successful implantation and delivery was increased for embryos with FF containing a high G-CSF concentration. There was a trend toward lower follicular G-CSF levels in cases of miscarriage. Therefore, follicular fluid volume cannot be a substitute for follicular G-CSF as a marker of embryo implantation ability.